Effect of moisture condition on mechanical behavior of low strength brick masonry - Sathiparan, N.; Rumeshkumar, U. (Elsevier, 2018)
The purpose of the research presented in this paper was to determine the influence of moisture on mechanical properties of brick, mortar and masonry. The strength of masonry structure was primarily influenced by a number of factors such as brick/block, bedding mortar, construction quality, pre/post environmental condition, etc. Among the factors affecting such behavior, the presence of moisture plays a key role in the deteriorating state of masonry structures. For this reason, in the present paper the compressive strength of bricks, cement mortars as well as compressive, shear and bond strength of masonry prisms are investigated, in oven-dry, air-dry and wet conditions. The experimental results demonstrate that moisture significantly reduces the compression strength of a brick and cement mortar; the greater the moisture content the lower compression strength. However, the compressive strength of masonry not improve in oven-dry condition, but reduce in wet condition. Moreover, shear and bond strength of masonry reduce with increase in moisture condition.
Keywords: Masonry; Brick